Δυσλειτουργικές πεποιθήσεις των εκπαιδευτικών για τον σχολικό εκφοβισμό και τη θυματοποίηση - Γαλανάκη, Ε. (Πρακτικά του 2ου Πανελλήνιου Συνεδρίου Επιστημών Εκπαίδευσης, 2011)
The aim of my participation in the Round Table entitled “Victimization and bullying in school (kindergarten, primary school, secondary school)” is to present a number of dysfunctional beliefs of educators about school bullying, which impede the implementation of preventive and interventive anti-bullying programs. Data are drawn from empirical research in various countries, and from recent Greek studies. Identifying and challenging these dysfunctional beliefs is a necessary first step before anti-bullying intervention, as it is well documented that the effectiveness of this intervention depends largely on the educator.